Logistics Service Accountabilities and Their Effects on Service Buyer's Trust - Kaynak, Ramazan; Avci, Salih Bortecine (Elsevier Science Bv, 2014)
This research aims to endeavour to bridge a gap in literature by examining accountability dimensions (logistics, financial, marketing, contractual, environmental) in third party logistics (3PL) service providers and the impact of such issues on buyer mist has been attempted to analyse. Towards this objective via the survey method 202 numbers of data have been collected from Turkey's food manufacturing companies. Data were collated and processed through analysis of variance and structural equation model to test the research hypotheses. The results show that logistics accountability, financial accountability and marketing accountability have positive effects on trust. The findings of the current study suggest that so long as 3PL service providers make their systems further accountable, they shall become more reliable. (C) 2013 The Authors. Published by Elsevier Ltd.
16th Meeting of the Euro-Working-Group-in-Transportation -- SEP, 2013 -- Porto, PORTUGAL
Keywords: Accountability; Buyer's Trust; Third party logistics service providers